Public memory and prison patrimony: Matters of present time Memória pública e patrimônio prisional: Questões do tempo presente - Borges V.T. (2018)
© 2018 RCN Publishing Company Ltd. All rights reserved.This article tries to question the processes of creating legacy related to public memory and prison patrimony. We discuss here the stress involved in choices on preservation and building of prisons while cultural patrimonies, by analyzing cases occurred in the XXth and XXIth Centuries in France, Portugal and United States, and then trying to connect them to Brazilian context. By approaching the dilemma between what is elected to be remembered and the creation of oblivion, we intend to reflect on public prison memory, by dialoguing with questions related to present time and public history.